The Measurement of the Zakat Utilization Index in the Smartfarm Academy Group - Chairunnisa, Lusy; Bahri, Efri Syamsul (Yayasan Mitra Peduli Indonesia, 2024)
This research aims to measure the zakat utilization index and analyze the impact of zakat utilization in the Smartfarm Academy group assisted by the Indonesian Zakat Initiative Amil Zakat Institute (LAZ IZI). This research uses quantitative methods with a descriptive approach. Data collection was carried out through surveys using questionnaires and interviews. Sample selection was carried out by purposive sampling. Data was collected based on the results of questionnaire answers and interviews with respondents, namely members of the Smartfarm Academy. Next, the data is processed using the Multi-Stage Weighted Index. The research results show that the zakat utilization index value in the Smartfarm Academy program in Tangerang Regency is 0.70 or is in the strengthening phase category. It shows that productive zakat is running according to the objectives and is right on target. This program has had a good impact on Mustahiq and social indicators as well as cultural, economic, da'wah, and environmental indicators. LAZ IZI, as the builder of this program, can replicate the Smartfarm Academy program to other Mustahiq groups so that the benefits are even more significant.